Analisis Faktor yang Mempengaruhi Perkembangan Kegiatan Komersial Di Koridor Jalan Kedungmundu Raya dan Sambiroto Raya - Diah Dhyeti Pradani; Ragil Haryanto (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Kedungmundu Raya and Sambiroto Raya goes to BWK VI, those corridors had an appeal for commercial actors in small-medium scale to invest/commercial activities. This research aims to determine and analyzed the factors affecting the development of commercial activities in Kedungmundu Raya and Sambiroto Raya streets in relations with territorial against new growth area of Kedungmundu-Sambiroto. This is a descriptive quantitative research. The road identifications showed that Segment 1 had quite rapid development indicated by land use change from non awakened into commercialized. Segment 2, had a significant changes, land use change from non awakened and occupancy into commercialized. Segment 3, had less significant changes, the changes are only functional from occupancy into commercialized. Segment 4 is the most significant development indicated by 3 supermarkets. While in the factor analysis, factors that affecting the development of commercial activity are Factor 1, accesibility, consist of majority of consumer, form of profit, main reasons and peak traffic. Factor 2, area suitability, consists of main reason and length of business. The most dominant factors is the area suitability.